"In Which the Partners Undertook Reciprocal Duties of Support" – A Discussion of the Phrase as Used in Bwanya v Master of the High Court, Cape Town: - Barratt, Amanda (Potchefstroom Electronic Law Journal, 2022)
In December 2021 the Constitutional Court delivered judgment in Bwanya v Master of the High Court, Cape Town. The court ruled that survivors of life-partnerships "in which the partners undertook reciprocal duties of support" would be entitled to claim benefits under the Maintenance of Surviving Spouses Act (the MSSA) and the Intestate Succession Act (the ISA). This case note focusses on the phrase "in which the partners undertook reciprocal duties of support." It examines the jurisprudential development of the phrase through the case law. It considers whether reliance on the phrase is likely to present an obstacle to potential claimants or whether the phrase can be interpreted in a way that broadens the protection provided by the MSSA and ISA so as to ensure that all vulnerable partners can be protected. The note suggests that the optimal way in which to interpret the requirement that the life-partners had undertaken reciprocal duties of support would be to focus on the claimant’s needs and financial dependence and to assess how the law can provide protection and redress to those who have incurred relationship-induced dependence as a consequence of the particular form and nature of the reciprocal support provided in the intimate relationship. Previous court judgments have noted the typically gendered nature of the contributions made by family members. The law must ensure that it furthers the constitutional goal of achieving substantive equality between men and women, while also acknowledging and responding to the intersectional forms that discrimination and disadvantage assumes.